2010
DOI: 10.1002/lary.21663
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Self‐image in Patients Undergoing Tracheostomy

Abstract: Planned tracheostomy is a beneficial intervention for patients with benign airway pathologies, since they experience an improvement in their physical health and the ability to perform activities of daily living. There is a decline in mental health postoperatively, which we attribute to worsening self esteem. Patients who did not undergo planned tracheostomy as seen in the retrospective group, experienced a decline in their physical and mental functioning. This can be attributed to the lack of understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 3 publications
1
24
0
2
Order By: Relevance
“…A study by Atlee et al showed that the quality of life of the cases with permanent pacemakers decreased in mental and social concepts a month after the implantation of a pacemaker and, no significant difference was observed in the physical aspects [ 29 ]. Furthermore, a study by Hashmi et al indicated that the quality of life of patients with tracheostomy decreased after the implantation of a tracheostomy in the absence of a proper education [ 5 ], which was consistent in this research. Therefore, the results of this study and the mentioned studies indicated that chronic patients, such as patients with tracheostomy who only received routine training in health centers for self-care, experienced a decrease in the quality of life; hence, more attention needed to be paid regarding the training of these patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A study by Atlee et al showed that the quality of life of the cases with permanent pacemakers decreased in mental and social concepts a month after the implantation of a pacemaker and, no significant difference was observed in the physical aspects [ 29 ]. Furthermore, a study by Hashmi et al indicated that the quality of life of patients with tracheostomy decreased after the implantation of a tracheostomy in the absence of a proper education [ 5 ], which was consistent in this research. Therefore, the results of this study and the mentioned studies indicated that chronic patients, such as patients with tracheostomy who only received routine training in health centers for self-care, experienced a decrease in the quality of life; hence, more attention needed to be paid regarding the training of these patients.…”
Section: Discussionsupporting
confidence: 90%
“…What should also be considered are the new circumstances in their lives, including an unpleasant change in their appearance and the limitations due to a tracheostomy. This group of patients may suffer from stress, low self-esteem, negative change in their appearance [ 5 ], difficulty in communicating effectively with others and isolation and, as a result, these can have an adverse effect on their quality of life [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is because there have been reports showing that tracheostomy has the potential to cause a significant decline in a patient's mental health, attributable to worsening self-esteem [12,14]. Therefore, if spine surgeons can present the possibility of later decannulation, patients would be more likely to accept subsequent therapy and the resulting situation.…”
Section: Discussionmentioning
confidence: 99%
“…The invasiveness secondary to tracheostomy is both physical and mental. It has been reported that there is a decline in a patient's mental health after tracheostomy, attributable to worsening self-esteem [12,14]. Therefore, it is important for patients to be aware about the possibility of decannulation, because this helps them to accept subsequent therapy and the resulting situation.…”
Section: Introductionmentioning
confidence: 99%
“…18 There is an inevitable reduction in the quality of life of patients following tracheostomy due to speech problems, body image issues, and daily physical limitations. 19 Therefore, the American Academy of Sleep Medicine recommended that tracheostomy should only be used when all other treatment options have been exhausted and failed or when clinically urgent. 20…”
Section: Tracheostomymentioning
confidence: 99%